The Economic Impact of Artificial Intelligence as a General Purpose Technology and Its Innovations in Economic Research - Wan, Yingliang; Tao, Hong; Zhao, Yiheng; Huang, Liqian (International Journal of Computer Science and Information Technology, 2025)
Artificial Intelligence (AI) is rapidly becoming a key driver of modern economic development, with its impact spanning multiple facets of both microeconomic and macroeconomic levels. At the microeconomic level, AI significantly alters consumer behavior and business operations by enhancing individual decision-making efficiency and optimizing internal corporate management. Simultaneously, as a General Purpose Technology (GPT), AI fosters productivity improvements, industrial structure transformations, and the emergence of new growth drivers at the macroeconomic level. This study systematically analyzes the application of AI across different economic agents, exploring its profound effects on the labor market, industrial organization, and innovation ecosystems.